On the controls of abundance for soil‐dwelling organisms on the Tibetan Plateau - Ke Zhao; Xin Jing; Nathan J. Sanders; Litong Chen; Yu Shi; Dan F. B. Flynn; Yonghui Wang; Haiyan Chu; Wenju Liang; Jin‐Sheng He (Ecosphere, 2017)
Abstract After decades of research, we are starting to understand more about why the number of species varies from place to place on the planet. However, little is known about spatial variation in abundance, especially for soil‐dwelling organisms. In this study, we aimed to disentangle the relative influences of climatic factors, soil properties, and plant diversity on the abundance of soil‐dwelling invertebrates (i.e., nematodes and soil arthropods) at 48 alpine grassland sites on the Tibetan Plateau. We found that the abundance of these two groups of soil organisms was negatively correlated with soil pH and temperature seasonality, and was positively correlated with soil organic carbon (SOC), mean annual precipitation, and plant species richness; there was no effect of mean annual temperature or seasonality in precipitation on the abundance of nematodes or soil‐dwelling arthropods. When we considered only the nematodes, we found that soil pH, mean annual precipitation, temperature seasonality, and SOC were the best predictors of abundance. However, plant species richness was the best predictor of the abundance of soil‐dwelling arthropods. Different orders within the arthropods responded differently to the suite of factors we examined. Taken together, our results suggest that increases in temperature alone might not alter the abundances of soil organisms in these alpine grasslands. Instead, altered precipitation regimes and increases in intra‐annual variation in temperature, changes in plant community diversity, and the resulting changes in soil characteristics (e.g., pH and organic carbon) could reshape soil communities in the Tibetan grassland ecosystems, and likely elsewhere on the planet.